Consumer preferences for sustainable and healthy lifestyle: Five-country discrete choice experiments - Milan Ščasný; Iva Zvěřinová; Vojtěch Máca (Charles University in Prague, Institute of Economic Studies (IES), 2019)
Consumers preferences for sustainable and healthier lifestyle are examined through stated preference discrete choice experiments. Specifically, we introduce several choice situations in which each respondent was asked to choose the best from three lifestyles presented, including the respondent's current lifestyle. Each lifestyle alternative is described by a different diet, health risks, and monetary costs. Diet is described by a number of portions of five different food items eaten per week (fruits and vegetables, meat, fish, legumes, and confectionery, ice-cream and sugar-sweetened drinks). Using a split-sample treatment, lifestyles are then described by either physical activities or environmental impacts (in kg of CO2 emissions). We also examine the effect of self-affirmation and information about the environmental impacts provided separately or in a combination. A non-linear preference is tested for increasing versus decreasing cost of food expenditures. Preferences are analysed using an original stated preference survey conducted in five EU countries (the Czech Republic, Latvia, Portugal, Spain, and in the United Kingdom) in summer 2018, with dataset consisting of 10,288 observations. We find that importance of lifestyle attributes varies across the countries and information treatments. The cost is significant in every country, indicating that lower costs lead to a higher probability of choosing the alternative lifestyle. Reducing health risks and environmental impact motivated respondents to change their lifestyle, even though reducing 1 kg CO2 due to food consumption a week is valued 3-6 times less than reducing cardiovascular risk by one percent. Still, the implied WTP for a tone CO2 abatement is in a range of 300-1,200 Euro and VSC of cardiovascular disease lies between 4,000 and 35,000 Euro, depending on country and DCE variant. Increasing physical activity increases the likelihood of changing lifestyle only in Latvia and Portugal. Most respondents prefer to keep eating meat and eliminating meat or fish from food consumption is associated with large dis-benefit. Respondents also prefer to increase portions of health-improving vegetables and fruits, however, this is not the case of pulses.
Keywords: D12; H31; Q51; R22; 330; Discrete choice experiment; willingness to pay; sustainable lifestyle; healthy diets; consumer preferences; physical activity; health risk; CO2 emissions